2020
DOI: 10.2196/19807
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Psychoeducational Apps for Military Members With Mild Traumatic Brain Injury: An Evaluation Utilizing the Mobile Application Rating Scale

Abstract: Background Military personnel have an elevated risk of sustaining mild traumatic brain injuries (mTBI) and postconcussion symptoms (PCS). Smartphone apps that provide psychoeducation may assist those with mTBI or PCS to overcome unique barriers that military personnel experience with stigma and access to health care resources. Objective This study aims to (1) use the Mobile Application Rating Scale (MARS) to evaluate smartphone apps purporting to provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Furthermore, given the range of available guidelines for mHealth technology development, the design of apps included in our review was unexpectedly poor. However, our findings are consistent with other mHealth research 27 suggesting that app design quality and content are not perfectly correlated and therefore raise important questions about barriers (e.g., cost 28 ) that may preclude apps from performing well in both domains. Among the problems we encountered were broken links, typos, fillable forms that did not fill correctly, inconsistent swipe functions across pages, and non-zoomable screens.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, given the range of available guidelines for mHealth technology development, the design of apps included in our review was unexpectedly poor. However, our findings are consistent with other mHealth research 27 suggesting that app design quality and content are not perfectly correlated and therefore raise important questions about barriers (e.g., cost 28 ) that may preclude apps from performing well in both domains. Among the problems we encountered were broken links, typos, fillable forms that did not fill correctly, inconsistent swipe functions across pages, and non-zoomable screens.…”
Section: Discussionsupporting
confidence: 86%
“…It was used in 38% (15/39) of papers as the sole means of quality evaluation [ 45 - 49 , 52 , 57 , 69 - 71 , 73 - 76 , 78 , 79 ]. MARS was also used in an additional 23% of papers along with other methodologies, such as clinical guidelines [ 46 , 55 , 56 , 58 , 65 , 67 , 68 , 77 , 81 ]. The breakdown of methodologies and the frequency of their use can be viewed in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Some of the qualitative responses indicated that participants felt this tool was for the purpose of improving their cognition or a brain game. This may be due to the myriad of tablet-based apps currently on the market being advertised as mHealth tools, despite limited evidence of their efficacy for improving cognitive status [ 24 ]. It is also possible that some participants experienced cognitive impairment that hindered their ability to fully comprehend the instructions and explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the potential differences in the relationship between the user and technology in a military context, the use of eHealth and mobile health (mHealth) innovations is becoming widespread within military and veteran populations [ 24 , 25 ]. This has been amplified by the recent COVID-19 pandemic when virtual health solutions have become increasingly common in all health care practices, including those in military environments.…”
Section: Introductionmentioning
confidence: 99%